A valid field test protocol of linear speed and agility in Rugby Union - Green, B. S.; Blake, C.; Caulfield, B. M. (The Journal of Strength and Conditioning Research, 2011)
Field testing is a key component to measure player performance in all sports, which provides coaches and strength and conditioning staff information to evaluate player performance and measure desired training effects. Therefore, the purpose of this study was to investigate the reliability and construct validity of a rugby union field test protocol based on analysis of the components of the game. Participants were placed in an Academy (n = 17) or Club (n = 11) group determined by current playing level. Trials of 10- and 30-m linear speed (LS), change of direction speed, and reactive agility speed were measured to evaluate the field test protocol's utility in distinguishing players of different playing abilities. Reliability analysis of each field test demonstrated stable values allowing this field test protocol to be used to compare between groups. Furthermore, the Academy players performed significantly (p < 0.05) faster compared to Club players in all LS and agility components. These results suggest that this field test protocol is appropriate to identify rugby union players of varying playing abilities allowing coaches and strength and fitness staff to measure a player's capability to execute critical aspects of the game and may have application in performance evaluation and talent identification. The results from this study suggest that this test battery is an appropriate measure in identifying the varying playing abilities of rugby union players. This enables coaches and fitness staff to assess a player's capability in executing critical aspects of the game and also may have application in performance evaluation and talent identification.